2021
DOI: 10.1016/j.pmedr.2021.101597
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviour in shift and non-shift workers: A systematic review and meta-analysis

Abstract: Research examining the prevalence, physical activity (PA) and sedentary behaviour (SB) in shift workers show mixed results. This systematic review and meta-analysis aimed to compare PA and SB in shift workers with non-shift workers following the PRISMA guidelines. Ebscohost megafile ultimate (CINHAL, E-journals, Academic search ultimate, health source consumer edition, SPORT Discus), PubMed, Scopus, Web of Science, and Science Direct databases were searched up to April 2021. Cross-sectional and baseline data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Until September 2021, none of the 122 reviews addressed the relationship between shift work and sedentariness after applying the eligibility criteria ( Supplementary Figure A ). However, when updating to September 2022, two systematic reviews were retrieved: one with meta-analysis ( 36 ) and one without meta-analysis ( 37 ) ( Supplementary Table I ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until September 2021, none of the 122 reviews addressed the relationship between shift work and sedentariness after applying the eligibility criteria ( Supplementary Figure A ). However, when updating to September 2022, two systematic reviews were retrieved: one with meta-analysis ( 36 ) and one without meta-analysis ( 37 ) ( Supplementary Table I ).…”
Section: Resultsmentioning
confidence: 99%
“…In the meta-analysis, Monnaatsie et al studied the prevalence of meeting physical activity guidelines, time spent in moderate-to-vigorous physical activity and in sedentary behavior ( 36 ). No significant difference was found in the prevalence of meeting physical activity guidelines and for the time spent in moderate-to-vigorous physical activity among shift-workers compared to non-shift workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have documented shift workers’ elevated risks for overall smoking [ 242 ], and are also more prone to smoke during their shifts, in order to stay awake, curb hunger and/or relieve stress [ 242 , 243 , 244 , 245 ]. Similarly, alcohol overconsumption has been documented in night or rotating shift nurses, potentially as a sleep aid [ 246 ], with decreased activity (exercise) [ 247 , 248 ]. These behaviors, together with pre-existing risk factors, such as elevated triglycerides [ 249 , 250 ], uncontrolled hypertension [ 236 , 239 ], and/or dyslipidemia [ 251 ], compounded by the physiological dysfunctions resulting from circadian disruption through shift work, may interact to promote a prediabetic state [ 233 ].…”
Section: Changing Environments Misaligned Circadian Rhythms and Resul...mentioning
confidence: 99%
“…Tammelin et al (2017) found on the basis of the same cross-national data that working nonstandard schedules was associated with increased time-based work-family conflict, but only among Finnish and British parents. Likewise, Murtorinne-Lahtinen et al (2016) found using qualitative interviews with Finnish mothers working nonstandard hours that unpredictable work schedules made it challenging to maintain daily routines in meals and coordinate daily activities in the family.…”
Section: Nonstandard and Unpredictable Working Time And Healthmentioning
confidence: 99%